IMPROVING STUDENTS 'CAPABILITIES TO MAXIMIZE, NEGOTIATING AND REALIZING NURSING PRACTICES NEONATUS BASED ON BIMA CULTURE THROUGH THE APPLICATION OF SUNRISE MODEL IN PKM ASAKOTA BIMA CITY: ACTION RESEARCH - Ade Wulandari; Ati Sulianty (poltekkes kemenkes mataram, 2016)
Abstract : Health nursing practice is a form of service to increase the degree of public health. By following the standards of nursing practice, a practitioner of nursing provides nursing care for clients as a whole in the aspect of biopsikososiokultural. A preliminary study undertaken through interviews with students of level III status of Bhima's DIII of nursing has been implementing the practice of Clinic Nursing Child II note that many found beliefs and practices of neonatal health care by the community based on tradition. Against the beliefs and practices of health care a newborn based on tradition, there are a few that can harm health and according to the beliefs of students in ways that do not comply with the concept of nursing that they get through coursework. This research is qualitative research using the method of the approach action researh. With menerapakan the Sunrise model through action research expected to identified problems faced by students in performing cross cultural nursing and care between the researcher and participants can together determine the method of solving the problem. The data in this study were obtained through interviews, observation and discussion in the Conference between the researcher and participants of the mini and more data analysis is intended to diagnose the problem and formulate a method of solving them follow the action research cycle. Research is conducted within one semester i.e. the semester even-numbered school year 2014/2015, which is the month of may until June 2015. Participants in this research is a student semester IV in Nursing Clinical Practice courses Children.